Prinsip Maslahah Pada Putusan Mahkamah Konstitusi Terhadap Perkawinan Bagi Umat Beragama Dan Penghayat Kepercayaan - Umar Haris Sanjaya; Agus Yudha Hernoko; Prawitra Thalib (Fakultas Hukum Universitas Islam Indonesia, 2021)
This study aims to provide insights on the Constitutional Court Decision Number 97 / PUU / XIV / 2016 on filling-in the space for religion or belief in the Identity Card (KTP) has maslahah value for the community. This can be declared true after an analysis of the objectives and their enforcement in Indonesia has been carried out. Maslahah values are manifested by the certainty of the beliefs contained in the KTP. So that in socializing, the people may know for sure one’s religion or belief to guarantee or minimize the occurrence of interfaith and belief marriages. This study uses a normative method with a statutory and conceptual approach. The results of the study conclude that the Constitutional Court's decision has maslahah principles in Islamic thought as it provides recognition of rights, recognition of access to rights to public services, public services on marriage registration as a form of certainty, is an order in the Marriage Law, legal certainty creates rights and obligations for spouses, marriage registration creates protection, the state is obliged to provide protection for its citizens